INTERNET ADDICTION DITINJAU DARI KETERAMPILAN SOSIAL PADA SISWA SMA PAB 6 MEDAN - Ayuni Syah Fitri; Ika Shabrina; Indah Fitriani; Juraidah J; Rina Mirza (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2019)
This study aims to determine the relationship between social skills and internet addiction. The hypothesis of this study states that there is a negative correlation between social skills and internet addiction, with the assumption that the higher social skills, the lower the internet addiction and conversely the lower social skills, the higher internet addiction. The subjects of the study are 127 student at SMA Persatuan Amal Bakti (PAB)6 Helvetia Medan Sumatera Utara Branch chosen by total disproportionate stratified random sampling method. Data were obtained from a scale for measuring social skills and internet addiction. The results of data analysis showed that the correlation coefficient was -0.535 with p 0.000 (p <0.05). It showed that there is a negative correlation between social skills and internet addiction. From these results, it is concluded that the hypothesisstating that there is a negative relationship between social skills with internet addiction, is acceptable.Keywords : Internet addiction, Social skills